Activating Inert MXenes for Hydrogen Evolution Reaction via Anchored Metal Centers. Issue 1 (23rd November 2021) - Tahini, Hassan A.; Tan, Xin; Smith, Sean C.
Abstract: Hydrogen evolution under alkaline conditions is still a challenge, due to the lack of active and cheap cathode materials. The reaction is controlled by the kinetics of water molecules dissociation, along with a balance between OH* desorption and H* recombination steps. The focus in this study is to investigate pathways to tune the activity of—the usually inert—MXenes via anchored metal atoms, which can act as active centers to facilitate the dissociation of water and the subsequent release of H2 molecules. The most promising candidates are Fe anchored on V2 CO2, Mn on Ti2 CO2 and V2 CO2 and Ir on Nb2 CO2 . These materials display low and facile H2 O dissociation, with barriers as low as 0.25 eV in some cases, and favorable OH* desorption steps. Abstract : Active, stable, and economically viable catalysts for the generation of hydrogen under alkaline conditions pose significant design challenges. Here it is reported on the use of Nb2 CO2, Ti2 CO2 and V2 CO2 MXenes, with metal dopants, which show great potential in overcoming major obstacles, such as poor water dissociation, paving the way for promising alkaline HER catalysts.